Prospects of Small-Scale Rice Processing Enterprise among Beneficiaries of Microfinance Loan in Nigeria’s Jigawa State - Sadiq, Mohammed; Salihu, Musa; Sani, Bashir (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2024)
The present study empirically determined the prospects of the rice value chain of paddy processors in Jigawa State of Nigeria. Despite the role of small-scale paddy rice processors as the main engine of growth of upstream rice value chain, and the growth and development of the rural economy in the study area, literature is undaunted with paucity of empirical information on the prospects of rice processing value chain in the study area. The study utilised cross-sectional data elicited through a well-structured questionnaire from a total of 200 processors (133 parboilers and 67 millers) selected through a multi-stage sampling technique. An easy cost-route approach was used for data collection during the 2022 processing period and the collected data were analysed using both descriptive and inferential statistics. Based on the empirical evidence, it is established that the rice processing potential has not been fully exploited in the study areas. In addition, it is evident that the rice processing enterprise is not only viable and profitable; it features good prospects in the supply value chain of rice in the study areas. However, to maintain the prospects in the supply value chain, the target actors must adopt a defensive mechanism, as inferred by the SPACE matrix.